Economics student teachers’ experiences-as-lived in a flipped pedagogical approach during crisis times - Van Wyk, Micheal M. (African Perspectives of Research in Teaching & Learning, 2022)
Scholars of teacher education had been reported phenomenology both as a philosophical and methodological construct in reporting students' experiences of learning. In recent decades, research studies on the flipped-class pedagogy strategy have shown that it has significant educational benefits for student learning across subjects and contexts. This research explores, describes, and gains insights into student teachers' experiences as lived during an online teaching course at an open distance e-learning (ODeL) university. An interpretive phenomenological lens was employed using virtual videoconferencing to collect data. A purposive sample of Bachelor of Education (BEd) and Postgraduate Certificate of Education (PGCE) student teachers were selected. This study contributes to the literature on pedagogical dimensions that drives the functionality of flipped learning in an ODeL context. Furthermore, this exploratory study contributes to the practical implementation of flipped learning. Future research may extend the inquiry to other pedagogical dimensions by examining the effect of motivational factors for example the self-efficacy of student teachers
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (3) (2022) Special Issue
Keywords: Phenomenology; Flipped Pedagogy; Pedagogical Dimensions; Interpretive Phenomenological Analysis; Semi-Structured Interviews; Teachers -- Training of; Phenomenology; Education -- Study and teaching; Economics -- Study and teaching